Effect of self-efficacy on sales performance of full-time life insurance industry - Bernadette Vidya Anthony Mohan (2008)
This paper attempts to establish whether self-efficacy and selected independent variables play a dominant role in the sales performance of life insurance agents in Singapore via self-administered questionnaires.